Strategi Komunikasi Pemerintah Desa dalam Upaya Pengembangan Objek Wisata Alam Aek Sijorni Kecamatan Sayurmatinggi Tapanuli Selatan - Harahap, Annisa Rosa Mora; Kholil, Syukur (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This research aims to analyze the communication strategy applied by the Aek Libung Village government in an effort to develop the natural attractions of Aek Sijorni, Sayurmatinggi District, South Tapanuli Regency. The method used is descriptive qualitative with a field study approach through observation, interviews, and documentation. The results showed that the village government's communication strategy was carried out through two approaches, namely formal and informal communication. Formal communication is realized in the form of coordination meetings, preparation of information modules, study tours, event cooperation, and distribution of promotional cards and brochures. Meanwhile, informal communication is carried out through social media-based digital promotions and mutual cooperation activities involving the community. Supporting factors for this strategy are Aek Sijorni's attractive natural potential and the use of information technology. The inhibiting factors include low community participation, inadequate road access, and dependence on natural conditions. The findings of this study show that the integration of formal and informal communication can increase the effectiveness of promotion and community participation. This research also contributes to the development of organizational communication theory in the context of village tourism.